THE PHILOSOPHY ON INSTITUTIONAL CHANGES OF STATE ISLAMIC HIGHER EDUCATION (PTKIN) INTO UNIVERSITY - Esha, Muhammad In'am (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
A policy can is inseparable Â from the philosophy that underlies and influences its actors. Institutional changes to university, we called as universitization, that occurred in State Islamic Higher Education (SIHE/PTKIN) can not be separated from the philosophy that surrounds it. Learning from the experience of Universitas Islam Negeri Maulana Malik Ibrahim Malang, as one of the IAIN that changed its institutional status from State Islamic College (SIC/STAIN) into the State Islamic University (SIU/UIN) can be reconstructed based on philosophy which became the foundation of the institutional change policy. The study found that the basic ideas are the universality of Islam, the philosophy of tarbiyah ulul albab, and the integration of science. The philosophy of institutional change can not be separated from the long history of reform thinking in Islam.